The Development of Using Lao Language for Communication of Teacher in Phonethong District, Luangprabang Province Academic year 2020 - 2021: https://doi.org/10.69692/SUJMRD0901168 - CHANHTHAHONG, Khamxay; SYSOUPHANH, Sangkhom; LITTHAVONG, Somvang; PATHOUMVANH, Phanthamanath; INVANHKHAM, Maiphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purposes of research are: 1) to develop the teaching of Lao language for communication for teachers at Phonthong secondary School, Phonethong District, Luang Prabang Province, 2). to examine the results of theteaching of Lao language for communication for teachers, and 3). to investigate the teachers’ satisfaction with the learning activities in teaching Lao language for communication for teachers at Phonthong secondary School, Phonethong District, Luang Prabang Province. This study model was the measurement of before and after the pilot activities which employed the one – Group Pretest – Posttest Design for data collection. The target group consisted of 23 Lao language teachers at Phonthong Secondary School, Phonthong District, Luangprabang Province for the academic year 2021. The instruments used for the study comprised of 1) lesson plans on the subject of Lao language for communication for teachers. 2) pre – post tests of training achievement, 3) a questionnaire for eliciting the teachers’ opinions concerning their satisfaction towards the learning activities on the Lao language teaching for communication for teachers, and 4) the assessment form of ability to speak the Lao language for trainees and the collected data was analyzed by means of calculating arithmetic mean, standard deviation and percentage. The result vealed that: 1. The learning activities using teaching the Lao language for communication for teachers as was statistically significant at 0.00 difference with the, mean (after learning) of 12.83 and S.D. of 2.33 (12.83, SD=2.33) which is higher than the mean ( before learning ) of 15.91 and S.D. of 1.96 (15.91, SD=1.96) which is in accordance with the established assumptions. 2. The participants showed the “highest” level of satisfaction towards the learning activities using the teaching of the Lao language for communication for (4.51, SD=0.61). However, when considering each aspect, it could be seen that the participants show the highest “highest” level of satisfaction towards the measurement and evaluation (4.56, SD= 0.60), followed by the environment aspect (4.55, SD= 0.53), teaching and learning activities, application, lesson content and teaching methods (4.50, SD= 0.54), (4.49, SD= 0.61), (4.46, SD= 0.61), (4.43, SD= 0.56) respectively, and they were also concistant with the established assumptions.